Evaluation of Regression in Epicardial Adipose Tissue Thickness on Cardiac MRI in Post-Acute Coronary Syndrome Patients - Syed, Syed Sajiddain; Khan, Muhammad Nadir; Chauhdry, Azhar Ali; Ghous, Muhammad Waleed; Ali, Gulzar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate changes in epicardial adipose tissue (EAT) on cardiac magnetic resonance imaging (CMRI) in patients treated for acute coronary syndrome (ACS) and to assess its association with the severity of coronary artery disease (CAD). Study Design: Prospective longitudinal study. Place and Duration of Study: Cardiology Department of Armed Forces Institute of Cardiology, National Institute of Heart Diseases, Rawalpindi, Pakistan; from Aug 2025 to Nov 2025. Methods: Overall, 102 ACS patients aged 18–65 years, underwent both PCI and cardiac magnetic resonance imaging (CMR) were enrolled through consecutive sampling. Prior CABG patients, patients with LVEF <40%, MRI contraindications, eGFR <30 mL/min/1.73m², or statin intolerance were excluded from study. EAT thickness was measured on baseline and 3-month follow-up CMR scans, with regression defined as ≥10% reduction in EAT thickness. Cardiovascular outcomes, included stroke, revascularization, heart failure, and mortality, and assessed at follow-up. Results: A total of 102 patients with a median age of 60(52.75-63.00) years were included, of whom 64(62.7%) were male. The median EAT thickness decreased from 0.48 mm (IQR: 0.42–0.58) at baseline to 0.45 mm (IQR: 0.40–0.53) at 3 months. The EAT regression was 0.03 mm (IQR: 0.05-0.02). This reduction was statistically significant (p<0.001). Which did not meet the predefined ≥10% regression criterion. The correlation between CAD severity and EAT regression was weaker but statistically significant (r=0.302, p=0.002). Conclusion: EAT thickness showed a strong positive correlation with CAD severity but did not demonstrate significant regression over three months.